DEFINITION AND FORMATION OF CORPORATE SOCIAL RESPONSIBILITY IN UKRAINE - Козьмук, Наталія (Modern engineering and innovative technologies, 2023)
The work examines the main theoretical aspects of the concepts of social responsibility in the context of business and corporate social responsibility. The need to combine profitable activities of the enterprise with activities that benefit society. The